A meta-analysis: elucidating diagnostic thresholds of peak systolic flow velocities in thyroid arteries for the discrimination of Graves’ disease and destructive thyrotoxicosis - Li, Sinong; Ding, Zheng; Li, Xiang; Fu, Miao; Sang, Li; Yang, Mingxia; Tang, Rubo; Gu, Tianxiang; Sang, Liang (Frontiers in Endocrinology, 2024)
Objective This meta-analysis examines peak systolic velocities (PSVs) in thyroid arteries as potential biomarkers for thyroid disorders, which includes treated and untreated Graves’ disease(GD) and destructive thyrotoxicosis(DT). Methods A search across databases including PubMed, Google Scholar, Embase, and Web of Science identified studies assessing peak systolic flow velocity in the inferior thyroid artery (ITA-PSV) and superior thyroid artery (STA-PSV) diagnostic efficacy in GD and DT.And the search was restricted to publications in the English language.The analysis compared STA-PSV and ITA-PSV across patient groups, evaluating intra-group variances and synthesizing sensitivity and specificity data. Results The analysis covered 18 studies with 1276 GD, 564 DT patients, and 544 controls. The difference of STA-PSV between GD group, DT group and normal group and the difference of ITA-PSV were analyzed in subgroups, and there was no statistical significance between subgroups when comparing any two groups. Normal subjects displayed intra-group ITA-PSV and STA-PSV differences with established cut-off values of 20.33 cm/s (95% CI, 17.48-23.18) for ITA-PSV and 25.61 cm/s (95% CI, 20.37-30.85) for STA-PSV. However, no significant intra-group differences were observed in the STA-PSV and ITA-PSV cut-off values among groups with GD or DT. The combined cut-off values for these patient groups and normal subjects were 68.63 cm/s (95% CI, 59.12-78.13), 32.08 cm/s (95% CI, 25.90-38.27), and 23.18 cm/s (95% CI, 20.09-26.28), respectively. The diagnostic odds ratio(DOR) for these values was 35.86 (95% CI, 18.21-70.60), and the area under the summary receiver operating characteristic (SROC) curve was 0.91, with a sensitivity estimate of 0.842 (95% CI, 0.772-0.866). Conclusion PSVs in thyroid arteries are useful diagnostic tools in distinguishing DT from GD. A PSV above 68.63 cm/s significantly improves GD diagnosis with up to 91% efficacy. No notable differences were found between superior and inferior thyroid arteries in these conditions.